The Guru's guide to SQL server stored procedures, XML, and HTML - Henderson, Ken (Addison-Wesley, 2002)
SQL Server developers worldwide raved about Ken Henderson's The Guru's Guide to Transact-SQL : its exceptionally clear, conversational explanations, and its powerfully useful projects and code examples. This book helps SQL Server developers take the next step -- building more powerful, robust applications than ever before. Henderson identifies several key areas of SQL Server development that offer the greatest power -- and then covers each of them in exceptional detail. The book includes especially thorough coverage of Transact-SQL stored procedure programming, including features such as extended procedures, database design, and XML that are often disregarded in competitive books. Henderson introduces a method he has developed to add arrays to T-SQL, something previously thought impossible. He offers an ideal balance of theory and code, gradually building on basic techniques to create increasingly sophisticated solutions, and teaching the philosophy of Transact-SQL programming alongside syntax and technique. An accompanying CD-ROM includes extensive source code, including valuable proprietary code that makes T-SQL queries run faster. For every SQL Server developer.